Environmental Flows for Hydropower Projects : Guidance for the Private Sector in Emerging Markets - World Bank Group (International Finance Corporation, Washington, DC, 2018)
This Good Practice Handbook is designed to provide guidance to practitioners on taking rigorous and consistent approaches to assess hydropower project impacts on downstream river ecosystems and people, and determine their Environmental Flows (EFlows) commitments. The Handbook outlines a good practice approach for integrating EFlows into hydropower projects, emphasizing the selection of context-appropriate EFlows Assessment methods. Its structure follows the main steps of this approach: 1. Understand the context of river functioning and the provision of ecosystem values and services into which EFlows will be introduced (Section 2); 2. Understand the potential downstream impacts associated with hydropower development (Section 3) and how these can be mitigated (Section 4); 3. Align ESIA and EFlows Assessments and ensure data sharing and good communication between the assessment teams (see Section 5); 4. Apply a context-appropriate EFlows Assessment method (Section 6); 5. Conduct a comprehensive and appropriate stakeholder engagement program leading to a decision on EFlows and other mitigation measures based on the outcome of the assessment (Sections 7 and 8); and 6. Prepare an Environmental Flow Management Plan (EFMP2; Section 9). It also provides the following: A logframe for integrating EFlows into hydropower plants (Section 10); and Case studies to illustrate the main concepts addressed in the Handbook (Section 11).